Оlena Giberman (Kareyeva), Nina Shargey and their impact on changes in Yu.V. Kondratyuk’s (O.G. Sharhey’s) biography:based on analysis of archival documents - I. О. Pistolenko (History of science and technology, 2018)
The article is devoted to the theme of returning to the history of science and technology of the real name of the Ukrainian scientist, one of the pioneers of the theory of astronautics, as well as an inventor, engineer in the construction of grain storage facilities, elevators and wind power Yu.V. Kondratyuk (O.G. Shargey).The circumstances that put the scientist before the need to take the name of another person and to sign his scientific and engineering developments are analyzed. On the basis of information from archival documents not yet entered into scientific circulation, the facts of the biography and the role played by O.P. Giberman (Kareyeva) and N.G. Shargey in this pro-cess and in the disclosure of the secret of the name change by Yury Kondratyuk (Olexander Shargey) are considered.